BCR/ABL1–like acute lymphoblastic leukemia: How to diagnose and treat?. Issue 2 (18th December 2018) - Chiaretti, Sabina; Messina, Monica; Foà, Robin
Abstract: BCR/ABL1 –like acute lymphoblastic leukemia (ALL) accounts for 15% to 30% of B‐lineage ALL, with a peak of incidence occurring in adolescence. This subgroup of patients is characterized by a peculiar transcriptional profile that resembles that of true BCR/ABL1 –positive cases, and have a heterogeneous genetic background and a poor outcome. Next‐generation sequencing studies have demonstrated that the majority of patients carry rearrangements of tyrosine kinases or cytokine receptors and mutations of janus kinase (JAK)/signal transducer and activator of transcription (STAT), thus opening the way to the possible use of targeted therapeutic approaches. However, several issues remain unresolved at both the diagnostic and therapeutic level, such as the definition of a standardized method to identify BCR/ABL1 –like ALL and the design of ad hoc clinical trials examining tyrosine kinase inhibitors or other tailored treatments. These aspects are discussed in this review. Abstract : Patients with BCR/ABL1 –like acute lymphoblastic leukemia are a poor‐prognosis subgroup who require identification of disease at the time of diagnosis to improve risk stratification, therapeutic decisions, and ultimately patient outcome. Several issues remain unsolved, including the lack of a standardized diagnostic assay with which to recognize patients with BCR/ABL1 –like acute lymphoblastic leukemia at the time of diagnosis, the impact of the BCR/ABL1 –like profile on minimal residual disease–guided clinical trials, and the best therapeutic approach for these patients.